Sette alphabeti di varie lettere - Ruano, Ferdinando, (European History and Culture - Book Archive pre-2000., 1971)
Rome, 1554. Facsimile 1971. Edition limited to 300 handnumbered copies. Typographical design: Aldert Witte.